The Effects of Science Intervention Material in the Academic Performance of Junior High School Students - Carlo Vincent J, Jordan (Future Science / FSH-PH Publications, 2021)
The researcher being a science teacher identified problems encountered by the students namely; low mean proficiency scores in science grade 10 during the first quarter examination, lack of interest during discussion and frequent absenteeism among students. The Division mean proficiency score target is 68 but the grade 10 students only obtained a score of 60 which is behind the target of the department. Science intervention material was conceptualized and created by the researcher based on the least mastered competencies. This material was utilized as intervention to address the problem of poor academic performance. The 15 respondents who received the science intervention material obtained M=27.9, SD=3.13 compared to the 15 respondents in the control group who obtained M=14.37, SD=9 demonstrated significantly better scores, t = - 21.29, p = <.00001. Intervention material based on least mastered competencies is an effective method of improving the academic performance of students